If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1(4 + -8x) = 4x + 2 5 + (4 * -1 + -8x * -1) = 4x + 2 5 + (-4 + 8x) = 4x + 2 Combine like terms: 5 + -4 = 1 1 + 8x = 4x + 2 Reorder the terms: 1 + 8x = 2 + 4x Solving 1 + 8x = 2 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 1 + 8x + -4x = 2 + 4x + -4x Combine like terms: 8x + -4x = 4x 1 + 4x = 2 + 4x + -4x Combine like terms: 4x + -4x = 0 1 + 4x = 2 + 0 1 + 4x = 2 Add '-1' to each side of the equation. 1 + -1 + 4x = 2 + -1 Combine like terms: 1 + -1 = 0 0 + 4x = 2 + -1 4x = 2 + -1 Combine like terms: 2 + -1 = 1 4x = 1 Divide each side by '4'. x = 0.25 Simplifying x = 0.25
| 4y+3X=197 | | 8/17dividedby10/6 | | 8/17/10/6 | | (-2c+3d/3c)+(9c-4d/9c)+2 | | 4-8+0= | | 3(x^2-64)=0 | | 1/2(6a | | 1/2(6a2-4a+5)= | | 4x-64906-488=2 | | 3(x^2-64)=00 | | 8-h/3=19 | | 9.4minusk=3 | | 0.8+0.47= | | y-128/0.8668 | | ydx-(3x+y^4)dy=0 | | 7/z+3=6/z-8 | | 2(c+6)=9c+2 | | 3/4y+5=-3/4y-9 | | (x^2+3y^2)dx+(2xy)dy=0 | | 3a+4b+2a+5+b= | | 71 3∙x=1.6÷6/11 | | 49=y^2 | | 1/4(7-x)=11/2 | | 1/4(7-x)=1/2 | | 3x-21=15 | | 108x+141y=3 | | 141x+108y=3 | | 6(1/2+x)=39 | | x-5/4x-2x+6/16x | | x^2+3x-10/x-2=3 | | -a+6x= | | 1/2(-12+x)=-31/2 |